Maladaptive Perfectionism and Academic Achievement in Indonesian Gifted Undergraduate Students: Goal Adjustment as Moderator - Fitriani Yustikasari Lubis; Lydia Freyani Hawadi; Rose Mini Agoes Salim; Urip Purwono (Psympathic : Jurnal Ilmiah Psikologi, 2020)
This paper examines the role of goal adjustment (goal disengagement and goal re-engagement) as a moderator of maladaptive perfectionism and academic achievement in Indonesian gifted undergraduate students. This cross-sectional study employs a mixed-method sequential explanatory approach. On the quantitative stage, eighty-six undergraduates identified as gifted students completed Frost Multidimensional Perfectionism Scale, Goal Adjustment Scale and self-reported GPA. On the qualitative stage, eight participants were selected from the quantitative stage to participate in a face to face interview. The result showed that maladaptive perfectionism negatively correlated with academic achievement. The interaction between maladaptive perfectionism and academic achievement moderated by goal disengagement show significant interaction, while goal re-engagement was not significant.